Diffuse lung disease in infancy and childhood: expanding the chILD classification. Issue 6 (9th October 2013) - Rice, Alexandra; Tran‐Dang, My‐Anh; Bush, Andrew; Nicholson, Andrew G
<x xml:space="preserve">Abstract</x> Aims Diffuse parenchymal lung diseases (DPLD) in children comprise a wide spectrum of rare disorders. In 2007 the Children's Interstitial Lung Disease (chILD) Research Cooperative proposed a classification system for DPLD in children <2 years of age. The aims of our study were to determine the utility and reproducibility of this system in children <2 years of age, and test its extension to 18 years of age. Methods and results Of 211 cases, 93 were <2 years of age at presentation and 58% were included in the chILD classification. In 118 cases aged between 2 and 18 years there was a wider distribution of disorders, overlapping with those seen in adults, necessitating expansion of the chILD classification types to encompass all reviewed cases, in particular patients with 'adult' diffuse lung diseases. Many cases showed mixed histological patterns, overlap often being between groups of disorders more prevalent in infancy. Concordance between reporting pathologists was 90%. Conclusions The chILD scheme allows classification of conditions more common in children <2 years of age. It can be applied to children of any age, although additional entities need to be included. We propose a more histologically based system for use when assessing biopsies in this context.